Investigating parameters of genetic algorithm and neural network on classic snake game - Yuen, Moo Chi; Yeong, Lee Wuan; Kang, Edmund Chen Yi; Syed, Shaheer Qaisar; Salam, Zailan Arabee Abdul (Journal of Applied Technology and Innovation, 2021)
Genetic Algorithm (GA) and Neural Network (NN) are implemented in a classic Snake game to produce an optimal snake that can achieve high scores. GA serves as a snake evolution operator, whereas NN serves as a moving direction determinator. In this paper, several crucial parameters of GA and NN are modified to observe the influence of each parameter to the Snake game. GA has population and mutation rate regarding to the modifiable parameters, meanwhile NN has hidden layer and hidden neuron. The experimental results show how the snake game performs after modifying the parameters.Key words- Naive Bayes algorithm, text classification, Multinomial Naive Bayes (MNB)